High-hardness impact-resistant acrylic plate and preparation method thereof

By using technical means such as high-strength modified polymers, modified fibers and composite antibacterial components in acrylic plates, the problem of insufficient hardness and wear resistance of traditional acrylic plates is solved, and the improvement of high hardness, impact resistance and antibacterial properties is achieved.

CN119875381AInactive Publication Date: 2025-04-25SHANDONG KELESI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510363457.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional acrylic plates have shortcomings in hardness and wear resistance, especially when they are subjected to mechanical stress or frequent friction, which is prone to scratches, wear or cracks, affecting the aesthetics and service life of the product.

Method used

High hardness impact-resistant acrylic plates were prepared by using components such as high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560. These components improve the mechanical properties, heat resistance and antibacterial properties of the materials through technical means such as graft modification and fluorine modification.

Benefits of technology

It significantly improves the hardness and wear resistance of the acrylic plate, while maintaining good transparency, processing performance and antibacterial properties, and extending the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of acrylic plates, in particular to a high-hardness impact-resistant acrylic plate and a preparation method thereof.Polymethyl methacrylate is subjected to graft modification through polycarbonate, the polycarbonate has excellent mechanical property and heat resistance, and the impact resistance of the acrylic plate is improved; a chain segment of polycarbonate is introduced into a molecular chain of polymethyl methacrylate through grafting modification, the tensile strength, impact strength and heat resistance of the material can be effectively improved, the overall mechanical property of the acrylic plate can be enhanced through modification, the weather resistance and aging resistance of the acrylic plate can be improved, and the service life of the acrylic plate is prolonged. The acrylic plate can still keep good appearance and performance after being exposed to an outdoor environment for a long time; through modification treatment of fluorine-modified polyurethane, the interface bonding force between the carbon fibers and a polymer matrix can be enhanced, the dispersity and stability of the carbon fibers in the acrylic plate are improved, and meanwhile, the acrylic plate can be endowed with excellent hydrophobicity and corrosion resistance due to introduction of the fluorine element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic plates, and in particular to a high-hardness impact-resistant acrylic plate and a preparation method thereof. Background Art

[0002] Acrylic sheet, as a widely used transparent or translucent thermoplastic material, has shown great application potential in many fields such as construction, furniture, advertising signs, automobile manufacturing, and electronic appliances due to its excellent light transmittance, good processing performance and excellent weather resistance. Although traditional acrylic sheets have many of the above advantages, they still have certain limitations in hardness and wear resistance. Especially in situations where they need to withstand large mechanical stress or frequent friction, their surfaces are prone to scratches, wear and even cracks, which seriously affects the appearance and service life of the product.

[0003] In order to overcome the shortcomings of traditional acrylic sheets in terms of hardness and wear resistance, technicians in this field have conducted a lot of research and exploration. A common practice is to enhance the mechanical properties of the material by adding inorganic fillers such as glass fiber and calcium carbonate, but these methods often lead to a decrease in the transparency of the material, increase the difficulty of processing, and have limited improvement in wear resistance. Another method is to use chemical modification methods, such as introducing functional groups or segments with high strength and wear resistance through copolymerization, grafting, etc. Although it can improve the hardness and wear resistance of acrylic sheets to a certain extent, it is often accompanied by increased costs and complicated preparation processes. In addition, with the improvement of people's health awareness, higher requirements are also put forward for the antibacterial properties of plastic products such as acrylic sheets. Although traditional antibacterial treatment methods such as adding antibacterial agents are effective, they may affect the transparency and mechanical properties of the material, and long-term antibacterial effects are difficult to guarantee.

[0004] Therefore, developing a new type of acrylic sheet that has high hardness and wear resistance while maintaining good transparency, processing performance and antibacterial properties has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] Technical issues solved In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-hardness impact-resistant acrylic plate and a preparation method thereof, aiming to prepare a new type of acrylic plate that has high hardness and wear resistance while maintaining good transparency, processing performance and antibacterial properties.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-hardness impact-resistant acrylic plate, the high-hardness impact-resistant acrylic plate is composed of the following components: high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560; The high-strength modified polymethyl methacrylate is obtained by grafting polymethyl methacrylate with polycarbonate; The modified carbon fiber is obtained by modifying carbon fiber powder with fluorine-modified polyurethane; The modified copolymer is prepared by grafting and modifying glycidyl methacrylate by treating basalt fiber with alkali.

[0008] Furthermore, the preparation steps of the high-strength modified polymethyl methacrylate are: Step A, weigh 35-38g of polymethyl methacrylate and 20-25g of polycarbonate, pour them into a torque rheometer, stir and mix at a temperature of 260°C, add 0.3-0.5g of dibutyltin dilaurate, stir and react at the original stirring speed for 20 minutes, and record the result as a blended product; Step B, mixing the blended product in step A with tetrahydrofuran at a solid-liquid ratio of 1:40 g / mL, heating and refluxing for 1 hour, pouring into ethyl acetate under stirring conditions for precipitation, stirring and dispersing, filtering to remove the filtrate and repeatedly washing with ethyl acetate for 3-5 times, and drying the obtained insoluble matter to obtain high-strength modified polymethyl methacrylate.

[0009] Furthermore, the stirring and mixing method in step A is stirring at a stirring speed of 60 r / min for 5 minutes, the stirring speed of the stirring condition in step B is 100 r / min, the stirring and dispersing method in step B is stirring at a stirring speed of 200 r / min for 3 hours, and the drying method in step B is placed in an oven at 45°C and dried for 3-5 hours.

[0010] Furthermore, the preparation steps of the modified carbon fiber are: Step 1, weigh 40-50g of dehydrated polypropylene glycol and 20-25g of isophorone diisocyanate and add them into a flask, drop 0.1-0.2g of dibutyltin dilaurate and heat to 80°C, stir and react at a stirring speed of 200r / min for 2h, then add 6-8g of 2,2-dihydroxymethylpropionic acid and continue to react for 2h, then add 22-26mL of acetone and cool to 60°C, the result is recorded as the reaction component; Step 2, add 4-5g of perfluorohexylethanol to the reaction components and continue to react for 2h, cool to 40°C, add 2-3g of triethylamine and continue to react for 30min, add 200-250mL of deionized water and stir at a stirring speed of 1000r / min for 30min, the obtained product is recorded as fluorine-modified polyurethane; Step 3, rotary evaporating the fluorine-modified polyurethane at a temperature of 50° C. for 2-3 hours, then adding deionized water to dilute it to a mass fraction of 10%, and then adding a leveling agent with a mass of 0.2% of the total amount of the emulsion, and dispersing it evenly to obtain a sizing agent component; Step 4, soak the carbon fiber powder in the sizing agent component according to a solid-liquid ratio of 1:100 g / mL, filter to remove the filtrate after soaking for 2-3 minutes, and dry it in an oven at 150°C for 10-20 minutes. Grind it through a 200-mesh sieve to obtain the modified carbon fiber.

[0011] Furthermore, the dehydration method in step 1 is to place the polypropylene glycol in a vacuum drying oven at 120° C. for dehydration for 3-6 hours, and the uniform dispersion method in step 3 is to stir at a stirring speed of 600 r / min for 10 minutes.

[0012] Furthermore, the preparation method of the alkali-treated basalt fiber is: The basalt fiber was immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL. After immersion for 20 minutes, the filtrate was filtered out and rinsed with deionized water until neutral. The fiber was dried in an oven at 58°C for 5-8 hours and then ground through a 100-mesh sieve to obtain alkali-treated basalt fiber.

[0013] Furthermore, the preparation method of the modified copolymer is: Pour 15-18g of alkali-treated basalt fiber, 30-35g of glycidyl methacrylate, 50-60g of deionized water, 3-4g of potassium persulfate and 2-3g of polyethylene glycol ether into a flask, heat to 90°C and stir to react for 3h, soak the obtained product in acetone for 30min and then wash it with deionized water 5 times, filter it and dry it in an oven at 80°C to constant weight, and the obtained product is the modified copolymer.

[0014] Furthermore, the preparation method of the composite antibacterial component is: Tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyldimethylbenzylammonium bromide and hexadecyltrimethylammonium bromide are weighed and mixed in equal weight ratio to obtain a composite antibacterial component.

[0015] A method for preparing a high-hardness impact-resistant acrylic sheet, the method for preparing the high-hardness impact-resistant acrylic sheet comprising: 3-5 parts by weight of modified carbon fiber, 5-6 parts by weight of modified copolymer, 1-2 parts by weight of composite antibacterial component, 1-2 parts by weight of antioxidant 1010 and 3-4 parts by weight of silane coupling agent KH-560 are weighed and mixed, poured into a ball mill for ball milling for 10 minutes, and then poured into a mixer filled with 90-100 parts by weight of high-strength modified polymethyl methacrylate for melt blending, and then poured into a mold for cooling and demolding to obtain a high-hardness impact-resistant acrylic sheet.

[0016] Furthermore, in the preparation method of the high-hardness impact-resistant acrylic sheet, the melt blending temperature is 190-200° C., the melt blending speed is 50 r / min, and the melt blending time is 10 min.

[0017] Beneficial Effects

[0018] The present invention provides a high-hardness impact-resistant acrylic plate and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention grafts polymethyl methacrylate with polycarbonate, and the polycarbonate has excellent mechanical properties and heat resistance. The polycarbonate chain segments are introduced into the molecular chain of polymethyl methacrylate by grafting modification, which can effectively improve the tensile strength, impact strength and heat resistance of the material. This modification can not only enhance the overall mechanical properties of the acrylic board, but also improve the weather resistance and anti-aging properties of the acrylic board, so that the acrylic board can still maintain good appearance and performance after long-term exposure to outdoor environment; through the modification treatment of fluorine-modified polyurethane, the interface bonding force between carbon fiber and polymer matrix can be enhanced, and the dispersion and stability of carbon fiber in acrylic board are improved. At the same time, the introduction of fluorine element can also give the acrylic board excellent hydrophobicity and corrosion resistance.

[0019] 2. The present invention uses alkali-treated basalt fiber to graft-modify glycidyl methacrylate. The basalt fiber has the advantages of high strength, high modulus, corrosion resistance and high temperature resistance. The alkali treatment can remove impurities and organic matter on the surface of the basalt fiber, improve its surface activity so that it can react with the epoxy group in glycidyl methacrylate to form a chemical bond. This grafting modification can not only enhance the compatibility between the basalt fiber and the polymer matrix, but also improve the mechanical properties and heat resistance of the copolymer. The prepared copolymer is added to the preparation of acrylic board, which can significantly improve the hardness and wear resistance of the material while maintaining its good transparency and processing performance. The composite antibacterial components in the present invention are all quaternary ammonium salt compounds with broad-spectrum antibacterial properties. Adding them to the preparation of acrylic board can give it good antibacterial properties and effectively prevent the growth and reproduction of bacteria and fungi.

[0020] 3. The high-hardness impact-resistant acrylic sheet prepared by the present invention can significantly improve the hardness and wear resistance of the acrylic sheet, and enhance its mechanical properties, heat resistance, weather resistance and antibacterial properties by introducing high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560. In addition, the present invention also improves the processing performance of the acrylic sheet by optimizing the preparation process, and can improve its processing efficiency and yield rate. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention will be further described below in conjunction with the embodiments.

[0023] The sources of some components in the embodiments and comparative examples are as follows: Polymethyl methacrylate, CP-75, ICI Company, UK; Polycarbonate, T-1260, Shanghai Zhonglian Chemical Plant; Dibutyltin dilaurate, analytical grade, Shandong Yuanjin New Materials Co., Ltd.; Tetrahydrofuran, Boten Technology (Yangzhou) Co., Ltd.; Ethyl acetate, Jiangsu Baiyunli Chemical Co., Ltd.; Polypropylene glycol, PPG-1000, Shanghai Titanco Technology Co., Ltd.; Isophorone diisocyanate, analytical grade, Shanghai Titan Technology Co., Ltd.; 2,2-Dihydroxymethylpropionic acid, analytical grade, Shanghai Titan Technology Co., Ltd.; Acetone, Maoming Runjing Chemical Co., Ltd.; Perfluorohexylethanol, analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd. Triethylamine, analytical grade, Shanghai Titan Technology Co., Ltd.; Leveling agent, BYK-333, analytical grade, BYK Chemical Company, Germany; Carbon fiber powder, Wuhan Jiyesheng Chemical Co., Ltd.; Sodium hydroxide, Jinan Hongqiao Chemical Co., Ltd.; Basalt fiber, Shandong Tonghui Glass Fiber Co., Ltd.; Glycidyl methacrylate, Jinan Kaichuang Chemical Co., Ltd.; Potassium persulfate, Jinan Shuangying Chemical Co., Ltd.; Polyethylene glycol ether, Shandong Poly Chemical Co., Ltd.; Tetradecyltrimethylammonium chloride, Hubei Shineng Chemical Technology Co., Ltd.; Dodecyltrimethylammonium bromide, Hubei Shineng Chemical Technology Co., Ltd.; Octadecyl dimethyl benzyl ammonium bromide, Hubei Shineng Chemical Technology Co., Ltd.; Hexadecyltrimethylammonium bromide, Hubei Shineng Chemical Technology Co., Ltd.; Antioxidant 1010, Shanghai Jingyan Chemical Co., Ltd.; Silane coupling agent KH-560, Hangzhou Jessica Chemical Co., Ltd.;

[0024] Example 1 A high-hardness impact-resistant acrylic sheet of this embodiment is composed of the following components: high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560; High-strength modified polymethyl methacrylate is prepared by grafting polymethyl methacrylate with polycarbonate, and the preparation steps are as follows: Step A, weighing 35g of polymethyl methacrylate and 20g of polycarbonate into a torque rheometer, stirring at a temperature of 260°C and a stirring speed of 60r / min for 5min, adding 0.3g of dibutyltin dilaurate, stirring at the original stirring speed for 20min, and recording the resultant as a blended product; Step B, mixing the blended product in step A with tetrahydrofuran at a solid-liquid ratio of 1:40 g / mL, heating and refluxing for 1 hour, pouring into ethyl acetate under stirring conditions at a stirring speed of 100 r / min for precipitation, stirring at a stirring speed of 200 r / min for 3 hours, filtering to remove the filtrate and repeatedly washing with ethyl acetate for 3 times, and the obtained insoluble matter is placed in an oven at 45° C. and dried for 3 hours to obtain high-strength modified polymethyl methacrylate.

[0025] The modified carbon fiber is obtained by modifying carbon fiber powder with fluorine-modified polyurethane, and the preparation steps are as follows: Step 1, weighing 40g of dehydrated polypropylene glycol and 20g of isophorone diisocyanate into a flask, dropping 0.1g of dibutyltin dilaurate, heating to 80°C, stirring at a stirring speed of 200r / min for 2h, adding 6g of 2,2-dihydroxymethylpropionic acid and continuing the reaction for 2h, then adding 22mL of acetone and cooling to 60°C, the result is recorded as the reaction component, and the dehydration method is to place the polypropylene glycol in a vacuum drying oven at 120°C for 3h; Step 2, add 4 g of perfluorohexylethanol to the reaction components and continue the reaction for 2 h, cool to 40°C, add 2 g of triethylamine and continue the reaction for 30 min, add 200 mL of deionized water and stir at a stirring speed of 1000 r / min for 30 min, and the obtained product is recorded as fluorine-modified polyurethane; Step 3, the fluorine-modified polyurethane was rotary evaporated at a temperature of 50° C. for 2 h, then deionized water was added to dilute it to a mass fraction of 10%, and then a leveling agent with a mass of 0.2% of the total amount of the emulsion was added, and the mixture was stirred at a stirring speed of 600 r / min for 10 min to obtain the sizing agent component; Step 4, soak the carbon fiber powder in the sizing agent component according to a solid-liquid ratio of 1:100 g / mL, filter to remove the filtrate after soaking for 2 minutes, and dry it in an oven at 150°C for 10 minutes. Grind it through a 200-mesh sieve to obtain the modified carbon fiber.

[0026] The modified copolymer is prepared by grafting glycidyl methacrylate onto basalt fiber treated with alkali.

[0027] The preparation method of alkali-treated basalt fiber is as follows: The basalt fiber was immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL. After immersion for 20 minutes, the filtrate was filtered out and rinsed with deionized water until neutral. The fiber was dried in an oven at 58°C for 5 hours and then ground through a 100-mesh sieve to obtain alkali-treated basalt fiber.

[0028] The preparation method of the modified copolymer is: 15 g of alkali-treated basalt fiber, 30 g of glycidyl methacrylate, 50 g of deionized water, 3 g of potassium persulfate and 2 g of polyethylene glycol ether were poured into a flask, heated to 90°C and stirred for reaction for 3 hours. The obtained product was soaked in acetone for 30 minutes and then washed with deionized water 5 times. After filtration, it was placed in an oven at 80°C and dried to constant weight to obtain a modified copolymer.

[0029] The preparation method of the composite antibacterial component is as follows: Tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyldimethylbenzylammonium bromide and hexadecyltrimethylammonium bromide are weighed and mixed in equal weight ratio to obtain a composite antibacterial component.

[0030] A method for preparing a high-hardness impact-resistant acrylic sheet, the method for preparing a high-hardness impact-resistant acrylic sheet is: 3 parts by weight of modified carbon fiber, 5 parts by weight of modified copolymer, 1 part by weight of composite antibacterial component, 1 part by weight of antioxidant 1010 and 3 parts by weight of silane coupling agent KH-560 were weighed and mixed, poured into a ball mill and ball milled for 10 minutes, and then poured into a mixer containing 90 parts by weight of high-strength modified polymethyl methacrylate for melt blending, and then poured into a mold for cooling and demolding, to obtain a high-hardness impact-resistant acrylic plate, wherein the melt blending temperature is 190°C, the melt blending speed is 50r / min, and the melt blending time is 10min.

[0031] Example 2 A high-hardness impact-resistant acrylic sheet of this embodiment is composed of the following components: high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560; High-strength modified polymethyl methacrylate is prepared by grafting polymethyl methacrylate with polycarbonate, and the preparation steps are as follows: Step A, weighing 38g of polymethyl methacrylate and 25g of polycarbonate into a torque rheometer, stirring at a temperature of 260°C and a stirring speed of 60r / min for 5min, adding 0.5g of dibutyltin dilaurate, stirring at the original stirring speed for 20min, and recording the resultant as a blended product; Step B, mixing the blended product in step A with tetrahydrofuran at a solid-liquid ratio of 1:40 g / mL, heating and refluxing for 1 hour, pouring into ethyl acetate under stirring conditions at a stirring speed of 100 r / min for precipitation, stirring at a stirring speed of 200 r / min for 3 hours, filtering to remove the filtrate and repeatedly washing with ethyl acetate for 5 times, and the obtained insoluble matter is placed in an oven at 45° C. and dried for 5 hours to obtain high-strength modified polymethyl methacrylate.

[0032] The modified carbon fiber is obtained by modifying carbon fiber powder with fluorine-modified polyurethane, and the preparation steps are as follows: Step 1, weighing 50g of dehydrated polypropylene glycol and 25g of isophorone diisocyanate into a flask, dropping 0.2g of dibutyltin dilaurate, heating to 80°C, stirring at a stirring speed of 200r / min for 2h, adding 8g of 2,2-dihydroxymethylpropionic acid and continuing the reaction for 2h, then adding 26mL of acetone and cooling to 60°C, the result is recorded as the reaction component, and the dehydration method is to place the polypropylene glycol in a vacuum drying oven at 120°C for 6h; Step 2, add 5 g of perfluorohexylethanol to the reaction components and continue the reaction for 2 h, cool to 40°C, add 3 g of triethylamine and continue the reaction for 30 min, add 250 mL of deionized water and stir at a stirring speed of 1000 r / min for 30 min, and the obtained product is recorded as fluorine-modified polyurethane; Step 3, the fluorine-modified polyurethane was rotary evaporated at a temperature of 50° C. for 3 h, then deionized water was added to dilute it to a mass fraction of 10%, and then a leveling agent with a mass of 0.2% of the total amount of the emulsion was added, and the mixture was stirred at a stirring speed of 600 r / min for 10 min to obtain the sizing agent component; Step 4, soak the carbon fiber powder in the sizing agent component according to the solid-liquid ratio of 1:100 g / mL, filter to remove the filtrate after soaking for 3 minutes, and dry it in an oven at 150°C for 20 minutes. Grind it through a 200-mesh sieve to obtain the modified carbon fiber.

[0033] The modified copolymer is prepared by grafting glycidyl methacrylate onto basalt fiber treated with alkali.

[0034] The preparation method of alkali-treated basalt fiber is as follows: The basalt fiber was immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL. After immersion for 20 minutes, the filtrate was filtered out and rinsed with deionized water until neutral. The fiber was dried in an oven at 58°C for 8 hours and then ground through a 100-mesh sieve to obtain alkali-treated basalt fiber.

[0035] The preparation method of the modified copolymer is: 18 g of alkali-treated basalt fiber, 35 g of glycidyl methacrylate, 60 g of deionized water, 4 g of potassium persulfate and 3 g of polyethylene glycol ether were poured into a flask, heated to 90°C and stirred for reaction for 3 hours. The obtained product was soaked in acetone for 30 minutes and then washed with deionized water 5 times. After filtration, it was placed in an oven at 80°C and dried to constant weight to obtain a modified copolymer.

[0036] The preparation method of the composite antibacterial component is as follows: Tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyldimethylbenzylammonium bromide and hexadecyltrimethylammonium bromide are weighed and mixed in equal weight ratio to obtain a composite antibacterial component.

[0037] A method for preparing a high-hardness impact-resistant acrylic sheet, the method for preparing a high-hardness impact-resistant acrylic sheet is: 5 parts by weight of modified carbon fiber, 6 parts by weight of modified copolymer, 2 parts by weight of composite antibacterial component, 2 parts by weight of antioxidant 1010 and 4 parts by weight of silane coupling agent KH-560 were weighed and mixed, poured into a ball mill for ball milling for 10 minutes, poured into a mixer containing 100 parts by weight of high-strength modified polymethyl methacrylate for melt blending, then poured into a mold for cooling and demolding, and the resultant was a high-hardness impact-resistant acrylic sheet, wherein the melt blending temperature was 200°C, the melt blending speed was 50 r / min, and the melt blending time was 10 min.

[0038] Example 3 A high-hardness impact-resistant acrylic sheet of this embodiment is composed of the following components: high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560; High-strength modified polymethyl methacrylate is prepared by grafting polymethyl methacrylate with polycarbonate, and the preparation steps are as follows: Step A, weighing 37g of polymethyl methacrylate and 23g of polycarbonate into a torque rheometer, stirring at a temperature of 260°C and a stirring speed of 60r / min for 5min, adding 0.4g of dibutyltin dilaurate, stirring at the original stirring speed for 20min, and recording the resultant as a blended product; Step B, mixing the blended product in step A with tetrahydrofuran at a solid-liquid ratio of 1:40 g / mL, heating and refluxing for 1 hour, pouring into ethyl acetate under stirring conditions at a stirring speed of 100 r / min for precipitation, stirring at a stirring speed of 200 r / min for 3 hours, filtering to remove the filtrate and repeatedly washing with ethyl acetate for 4 times, and the obtained insoluble matter is placed in an oven at 45° C. and dried for 4 hours to obtain high-strength modified polymethyl methacrylate.

[0039] The modified carbon fiber is obtained by modifying carbon fiber powder with fluorine-modified polyurethane, and the preparation steps are as follows: Step 1, weighing 45g of dehydrated polypropylene glycol and 22g of isophorone diisocyanate into a flask, dropping 0.2g of dibutyltin dilaurate, heating to 80°C, stirring at a stirring speed of 200r / min for 2h, adding 7g of 2,2-dihydroxymethylpropionic acid and continuing the reaction for 2h, then adding 24mL of acetone and cooling to 60°C, the result is recorded as the reaction component, and the dehydration method is to place the polypropylene glycol in a vacuum drying oven at 120°C for 5h; Step 2, add 5 g of perfluorohexylethanol to the reaction components and continue the reaction for 2 h, cool to 40°C, add 3 g of triethylamine and continue the reaction for 30 min, add 230 mL of deionized water and stir at a stirring speed of 1000 r / min for 30 min, and the obtained product is recorded as fluorine-modified polyurethane; Step 3, the fluorine-modified polyurethane was rotary evaporated at a temperature of 50° C. for 3 h, then deionized water was added to dilute it to a mass fraction of 10%, and then a leveling agent with a mass of 0.2% of the total amount of the emulsion was added, and the mixture was stirred at a stirring speed of 600 r / min for 10 min to obtain the sizing agent component; Step 4, soak the carbon fiber powder in the sizing agent component according to the solid-liquid ratio of 1:100 g / mL, filter to remove the filtrate after soaking for 3 minutes, and dry it in an oven at 150°C for 15 minutes. Grind it through a 200-mesh sieve to obtain the modified carbon fiber.

[0040] The modified copolymer is prepared by grafting glycidyl methacrylate onto basalt fiber treated with alkali.

[0041] The preparation method of alkali-treated basalt fiber is as follows: The basalt fiber was immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL. After immersion for 20 minutes, the filtrate was filtered out and rinsed with deionized water until neutral. The fiber was dried in an oven at 58°C for 7 hours and then ground through a 100-mesh sieve to obtain alkali-treated basalt fiber.

[0042] The preparation method of the modified copolymer is: 17 g of alkali-treated basalt fiber, 33 g of glycidyl methacrylate, 55 g of deionized water, 4 g of potassium persulfate and 3 g of polyethylene glycol ether were poured into a flask, heated to 90°C and stirred for reaction for 3 hours. The obtained product was soaked in acetone for 30 minutes and then washed with deionized water 5 times. After filtration, it was placed in an oven at 80°C and dried to constant weight to obtain a modified copolymer.

[0043] The preparation method of the composite antibacterial component is as follows: Tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyldimethylbenzylammonium bromide and hexadecyltrimethylammonium bromide are weighed and mixed in equal weight ratio to obtain a composite antibacterial component.

[0044] A method for preparing a high-hardness impact-resistant acrylic sheet, the method for preparing a high-hardness impact-resistant acrylic sheet is: 4 parts by weight of modified carbon fiber, 5 parts by weight of modified copolymer, 2 parts by weight of composite antibacterial component, 1 part by weight of antioxidant 1010 and 4 parts by weight of silane coupling agent KH-560 were weighed and mixed, poured into a ball mill and ball milled for 10 minutes, and then poured into a mixer containing 95 parts by weight of high-strength modified polymethyl methacrylate for melt blending, and then poured into a mold for cooling and demolding, to obtain a high-hardness impact-resistant acrylic sheet, wherein the melt blending temperature is 195°C, the melt blending speed is 50r / min, and the melt blending time is 10min.

[0045] Comparative Example 1 The high-hardness impact-resistant acrylic plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the high-strength modified polymethyl methacrylate in Example 1 is replaced with unmodified polymethyl methacrylate.

[0046] Comparative Example 2 The high-hardness impact-resistant acrylic plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified carbon fiber in Example 1 is replaced with unmodified carbon fiber.

[0047] Comparative Example 3 The high-hardness impact-resistant acrylic plate and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified copolymer in Example 1 is replaced with glycidyl methacrylate.

[0048] Comparative Example 4 The high-hardness impact-resistant acrylic board and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 4, the composite antibacterial component in Example 1 is replaced with tetradecyltrimethylammonium chloride.

[0049] Performance Testing The high-hardness impact-resistant acrylic sheets prepared in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-4 is tested. The specific testing methods and test items are as follows: 1. The wear resistance of Examples 1-3 and Comparative Examples 1-4 was tested with reference to the standard of HG / T43.3-2012, wherein the gloss loss rate = (gloss before friction - gloss after friction) / gloss before friction. The gloss was tested with a gloss meter, and the obtained data were recorded in the following table; 2. The impact strength of Examples 1-3 and Comparative Examples 1-4 was tested according to the ISO179 / 1eU standard, and the obtained data are recorded in the following table; 3. The tensile strength of Examples 1-3 and Comparative Examples 1-4 was tested according to the ISO527 standard, and the obtained data were recorded in the following table; 4. The comprehensive antibacterial rates of Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard of GB / T31402-2015, and the obtained data are recorded in the following table;

[0050] It can be seen from the data in the above table that the mechanical properties, wear resistance and antibacterial properties of the high-hardness impact-resistant acrylic sheets in Examples 1-3 are better than those in Comparative Examples 1-4, indicating that adding high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer and composite antibacterial component in the preparation of acrylic sheets can improve the performance of acrylic sheets.

[0051] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-hardness impact-resistant acrylic sheet, characterized in that: The high-hardness impact-resistant acrylic sheet is composed of the following components: high-strength modified polymethyl methacrylate, modified carbon fiber, modified copolymer, composite antibacterial component, antioxidant 1010 and silane coupling agent KH-560; The high-strength modified polymethyl methacrylate is obtained by grafting polymethyl methacrylate with polycarbonate; The modified carbon fiber is obtained by modifying carbon fiber powder with fluorine-modified polyurethane; The modified copolymer is prepared by grafting and modifying glycidyl methacrylate by treating basalt fiber with alkali.

2. The high-hardness impact-resistant acrylic sheet according to claim 1, characterized in that: The preparation steps of the high-strength modified polymethyl methacrylate are: Step A, weigh 35-38g of polymethyl methacrylate and 20-25g of polycarbonate, pour them into a torque rheometer, stir and mix at a temperature of 260°C, add 0.3-0.5g of dibutyltin dilaurate, stir and react at the original stirring speed for 20 minutes, and record the result as a blended product; Step B, mixing the blended product in step A with tetrahydrofuran at a solid-liquid ratio of 1:40 g / mL, heating and refluxing for 1 hour, pouring into ethyl acetate under stirring conditions for precipitation, stirring and dispersing, filtering to remove the filtrate and repeatedly washing with ethyl acetate for 3-5 times, and drying the obtained insoluble matter to obtain high-strength modified polymethyl methacrylate.

3. The high-hardness impact-resistant acrylic sheet according to claim 2, characterized in that: The stirring and mixing method in step A is stirring at a stirring speed of 60 r / min for 5 minutes, the stirring speed of the stirring condition in step B is 100 r / min, the stirring and dispersing method in step B is stirring at a stirring speed of 200 r / min for 3 hours, and the drying method in step B is drying in an oven at 45°C for 3-5 hours.

4. The high-hardness impact-resistant acrylic sheet according to claim 1, characterized in that: The preparation steps of the modified carbon fiber are: Step 1, weigh 40-50g of dehydrated polypropylene glycol and 20-25g of isophorone diisocyanate and add them into a flask, drop 0.1-0.2g of dibutyltin dilaurate and heat to 80°C, stir and react at a stirring speed of 200r / min for 2h, then add 6-8g of 2,2-dihydroxymethylpropionic acid and continue to react for 2h, then add 22-26mL of acetone and cool to 60°C, the result is recorded as the reaction component; Step 2, add 4-5g of perfluorohexylethanol to the reaction components and continue to react for 2h, cool to 40°C, add 2-3g of triethylamine and continue to react for 30min, add 200-250mL of deionized water and stir at a stirring speed of 1000r / min for 30min, the obtained product is recorded as fluorine-modified polyurethane; Step 3, rotary evaporating the fluorine-modified polyurethane at a temperature of 50° C. for 2-3 hours, then adding deionized water to dilute it to a mass fraction of 10%, and then adding a leveling agent with a mass of 0.2% of the total amount of the emulsion, and dispersing it evenly to obtain a sizing agent component; Step 4, soak the carbon fiber powder in the sizing agent component according to a solid-liquid ratio of 1:100 g / mL, filter to remove the filtrate after soaking for 2-3 minutes, and dry it in an oven at 150°C for 10-20 minutes. Grind it through a 200-mesh sieve to obtain the modified carbon fiber.

5. The high-hardness impact-resistant acrylic sheet according to claim 4, characterized in that: The dehydration method in step 1 is to place the polypropylene glycol in a vacuum drying oven at 120° C. for dehydration for 3-6 hours, and the uniform dispersion method in step 3 is to stir at a stirring speed of 600 r / min for 10 minutes.

6. The high-hardness impact-resistant acrylic sheet according to claim 1, characterized in that: The preparation method of the alkali-treated basalt fiber is: The basalt fiber was immersed in a 10% sodium hydroxide solution at a solid-liquid ratio of 1:20 g / mL. After immersion for 20 minutes, the filtrate was filtered out and rinsed with deionized water until neutral. The fiber was dried in an oven at 58°C for 5-8 hours and then ground through a 100-mesh sieve to obtain alkali-treated basalt fiber.

7. The high-hardness impact-resistant acrylic sheet according to claim 1, characterized in that: The preparation method of the modified copolymer is: Pour 15-18g of alkali-treated basalt fiber, 30-35g of glycidyl methacrylate, 50-60g of deionized water, 3-4g of potassium persulfate and 2-3g of polyethylene glycol ether into a flask, heat to 90°C and stir to react for 3h, soak the obtained product in acetone for 30min and then wash it with deionized water 5 times, filter it and dry it in an oven at 80°C to constant weight, and the obtained product is the modified copolymer.

8. The high-hardness impact-resistant acrylic sheet according to claim 1, characterized in that: The preparation method of the composite antibacterial component is: Tetradecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyldimethylbenzylammonium bromide and hexadecyltrimethylammonium bromide are weighed and mixed in equal weight ratio to obtain a composite antibacterial component.

9. A method for preparing a high-hardness impact-resistant acrylic sheet according to any one of claims 1 to 8, characterized in that: The preparation method of the high-hardness impact-resistant acrylic sheet is as follows: 3-5 parts by weight of modified carbon fiber, 5-6 parts by weight of modified copolymer, 1-2 parts by weight of composite antibacterial component, 1-2 parts by weight of antioxidant 1010 and 3-4 parts by weight of silane coupling agent KH-560 are weighed and mixed, poured into a ball mill for ball milling for 10 minutes, and then poured into a mixer filled with 90-100 parts by weight of high-strength modified polymethyl methacrylate for melt blending, and then poured into a mold for cooling and demolding to obtain a high-hardness impact-resistant acrylic sheet.

10. The method for preparing a high-hardness impact-resistant acrylic sheet according to claim 9, characterized in that: In the preparation method of the high-hardness impact-resistant acrylic plate, the melt blending temperature is 190-200° C., the melt blending speed is 50 r / min, and the melt blending time is 10 min.

Citation Information

Patent Citations

  • Composite material containing modified basalt fiber and polymer and preparation method thereof

    CN103044877A

  • High-impact, self-lubricating and excellent-wear-resistance carbon fiber reinforced PMMA composite material and preparation method thereof

    CN111423682A

  • Formula and preparation method of nano physical composite bactericidal and bacteriostatic agent

    CN112106785A

  • High-strength wear-resistant mobile phone rear cover material and preparation method thereof

    CN118165491A

Cited By

  • Continuous casting high-hardness acrylic plate and preparation method thereof

    CN120718306A